Pengaruh Komitmen Hijau dan Green Intellectual Capital Terhadap Kinerja keberlanjutan Perusahaan Pertambangan Batu Bara di Indonesia - Wulandari, Sepia Tri; Saputra, Praja Hadi; Pribadi, Muhammad Iqbal (Balance : Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of green commitment and Green Intellectual Capital on sustainability performance. The research was conducted using a quantitative approach and secondary data. This study used 34 coal mining companies listed on the Indonesia Stock Exchange, selected using purposive sampling during the period 2020-2023. Data analysis was performed using multiple linear regression, supplemented by descriptive statistical tests and classical assumption tests. The results of the study indicate that green commitment has a positive but insignificant effect on sustainability performance. Similarly, Green Intellectual Capital also has a positive but insignificant effect on sustainability performance.